The European Court of Human Rights : Implementing Strasbourg's Judgments on Domestic Policy. - Anagnostou, Dia (Edinburgh University Press, 2013)
Since the turn of the millenium, the European Court of Human Rights (ECtHR) has been the transnational setting for a European-wide 'rights revolution'. This book aims to contribute to a flourishing scholarship on human rights, courts and legal processes, and their consequences for national politics. Adopting an inter-disciplinary perspective, it considers the domestic implementation of ECtHR judgments, and their impact upon national laws, policies and institutions.